Surfactant Assisted Electrospray Ionization Time of Flight Mass Spectrometry of Synthetic Polymers - Brooks, James L. (East Carolina University, 2010)
Synthetic polymers are complex mixtures which often require extensive characterization to determine chemical composition and structure. Mass spectrometric techniques have greatly enhanced the quantity, as well as the quality, of data that can be used to characterize synthetic polymers. Electrospray Ionization Mass Spectrometry, ESI-MS, is capable of providing a wealth of information on biomolecules, inorganic compounds, and small synthetic polymer (molecular weight less than 3,000 g/mol). While ESI-MS has proven to be a powerful characterization technique for small synthetic polymers its tendency to generate multiply charged ions results in very complex data for higher molecular weight synthetic polymers and yields data that is too complicated for complete analysis. A means to simplify the data obtained for ESI-MS characterization of large synthetic polymers by reducing multiple charging and increasing signal to noise ratio of the singly charged analyte ions would be of substantial use.  Singly charged poly (methyl methacrylate) ions with weight average molecular weights 4,000, 8,000 and 12,000 g/mol were observed by adding a surfactant (cetyltrimethylammonium bromide) and changing critical ESI conditions. Altering these parameters, as well as others, has played an important role of reducing the overall charging that the analyte may gain during the desolvation process.
Keywords: Chemistry, Analytical; Analytical chemistry; Electrospray ionization mass spectrometry; Polymers; Surface active agents